(untitled) (Південний архів (історичні науки), 2022)
Purpose and methodology of the study. The article analyzes criminal investigation cases on the Bashtansky region of the Nikolayev area. The main goal is to identify the sentiments and reactions of the peasants to the actions of the authorities that provoked the artificial famine in Ukraine based on the analysis of criminal investigations in 1932–1933 . In the context of the study, criminal investigative cases are not only an indicator of the scale of the punitive system of government, but also evidence of public sentiment, the reaction of people to the totalitarian regime. Research of archival materials is based on a systematic approach and structural and functional analysis. The solution of the set goal is realized at the expense of historical-situational, historical- chronological, biographical, retrospective methods. Results and conclusions of the study. Since the proclamation of Ukraine’s independence, there have been many scholarly works on the Holodomor, as well as the mass repression that accompanied the artificial famine. The Nikolaev historians carried out the detailed analysis of a source base about the Holodomor of 1932–1933 , covered the reasons, consequences of the artificial Holodomor, its features in the territory of the Nikolaev area. A community representative at the district level joined this work. The value of their research lies in the creation of an information block based on the memories of eyewitnesses, the discovery of burial sites, photographic documents. On the other hand, the work of researchers does not fully cover and analyze the problem of protest mood of people who are on the verge of survival. The mood of the Ukrainian peasantry, which can be described as protest, has been identified. Based on the analysis of criminal investigation cases, several variants of resistance of the residents of the villages of the Bashtansky district to the punitive actions of the communist authorities were identified. The first type is passive resistance, which manifested itself in attempts to hide part of the harvest from total confiscation. Such a reaction is characteristic not only of individual peasant farms and families. The heads of the collective farms and members of the board also tried to leave the harvest in their village by various methods and prevent it from being taken away. The second type is active resistance, which is manifested in the dissemination of objective information about the situation, attempts to organize riots against the government and direct demonstrations of the peasants. Undoubtedly, the Ukrainian people, which faced many trials in the first decades of the twentieth century – the First World War, revolutions, civil war, famine of 1921–1923, repeated changes of power and political course, transformation of political, economic, cultural space – was exhausted. But this does not mean that people have lost the thirst for life, the desire for freedom and unquestioningly, like lambs, went to the slaughter. Ukrainians were not ready to accept the punitive policy of the authorities. This thesis is confirmed by numerous criminal investigations in which citizens were accused of anti-Soviet agitation, calls and preparations for riots against the government, attempts to overthrow it.